Intellectual Capital and Efficiency Performance of Malaysian Islamic and Conventional Banking Sector - Abdul Alim, Dee (Universiti Malaysia Sarawak (UNIMAS), 2019)
The services sector, especially on banking industry, had played vital roles for development that contribute most towards Gross Domestic Product rather relatively to other sectors. Nonetheless, perspective in intellectual capital was essential and highly recommended especially in developing countries such as Malaysia. Therefore, the general objective of the study is to investigate the relationship between Value Added Intellectual Capital (VAIC) and technical efficiency performance of Malaysian Islamic and conventional banking sectors. The scenarios lead to the specific objectives namely to investigate major components of intellectual capital namely human capital efficiency, structural capital efficiency, and capital employed efficiency with the technical efficiency performance for Islamic and conventional banks in Malaysia over the period of 2007 to 2016. Another specific objective is to examine the sources of intellectual capital as well as to assess the nexus between intellectual capital and efficiency performance of Malaysian banks. The results of the study show that human capital efficiency and capital employed efficiency are a positive relationship with significant efficiency. However, there was a negative relationship between structural capital efficiency with technical efficiency performance. The results suggested that the Malaysian bank should enhance the ability of human capital and capital employed to sustain the efficiency performance of the banks. Keywords: Intellectual capital, technical efficiency, Islamic bank, conventional bank